Figuring Kierkegaard’s Religious Individual - Martinez, Roy (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2003)
In Kierkegaard’s scheme of concepts, acts of piety and ascetic styles of living — however colorful and conspicuous their ostensible forms — do not eo ipso constitute the religious individual. There is more. According to the logic of this train of thought, no one can know who is a religious individual. To aggravate matters, this blessed ignorance pertains also to the very person who would in all sincerity arrogate such an identity. So, at least, run strains of a theory adumbrated, for example, in Training in Christianity, The Concept of Anxiety and Concluding Unscientific Postscript.